Implementasi Filter Finite Impuls Response (FIR) pada DSK TMS320C6713 Transceiver Menggunakan Teknik Windowing - Adella Acqha Vico Addina (Jurnal Jaringan Telekomunikasi, 2018)
In this study, implementing the FIR filter with the Blackman window and Rectangular window methods with the types of low pass, highpass, and bandpass filters using 2 DSK TMS320C6713 boards as sender (Tx) and receiver (Rx) using the code composer studio (CCS) V software program. .3.1, which will then be displayed on Matlab to observe the output results. From the test results, data will be obtained which are then analyzed to determine the filter performance of the design results and the real implementation results using the DSK TMS320C6713. The results showed that the design of the low pass, high pass and bandpass filters was in accordance with the desired specifications, although in the highpass filter design, the filter results were still incomplete.